Pengaruh Self-Leadership, Fleksibilitas Waktu Kerja, Kesehatan Mental, dan Motivasi Kerja terhadap Kinerja Karyawan pada PT. Bestindo Car Utama - Rima Apriliani; Yuni Kasmawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to determine the influence of Self-leadership (X1), Work Time Flexibility (X2), Mental Health (X3), and Work Motivation (X4) on Employee Performance (Y) at PT Bestindo Car Utama. The research employs a quantitative approach with non-probability sampling. The sample consists of 63 respondents who are active employees of the company. Data were collected through questionnaires and analyzed using descriptive statistics for primary data and inferential analysis with SmartPLS v.4.1.1.4 software. The results show that Self-leadership and Work Time Flexibility have no significant effect on Employee Performance. However, Mental Health and Work Motivation have a positive and significant effect on Employee Performance. These findings indicate that psychological and motivational aspects play an important role in improving employee productivity. Therefore, the company needs to pay greater attention to mental well-being and the factors that can enhance employee motivation to achieve optimal performance. This research is expected to serve as a reference for organizations in designing human resource policies oriented toward performance improvement through well-being and motivation-based approaches.